Dual-action potential of cationic cryptides against infections and cancers - Amr Adel, Ahmed Abd El-Aal *; Fairen, Angelin Jayakumar *; Kavita, Reginald * (Elsevier, 2023)
Cryptides are a subfamily of bioactive peptides embedded latently in their parent proteins and have multiple biological functions. Cationic cryptides could be used as modern drugs in both infectious diseases and cancers because their mechanism of action is less likely to be affected by genetic mutations in the treated cells, therefore addressing a current unmet need in these two areas of medicine. In this review, we present the current understanding of cryptides, methods to mine them sustainably using available online databases and prediction tools, with a particular focus on their antimicrobial and anticancer potential, and their potential applicability in a clinical setting.